PENGARUH PROMOSI KESEHATAN TENTANG POSYANDU LANSIA TERHADAP KEAKTIFAN LANSIA DI POSYANDU LANSIA (Studi Eksperimental di Dusun Paron II, Wilayah Kerja Puskesmas Ngasem) - Sumirat, Widhi (Akademi Keperawatan Pamenang, 2011)
Posyandu for Elderly is the unit developed by government policies that operated by health care tenagers and cadre through health programs aimed at increasing coverage of health services in accordance with the needs of the elderly. With health promotion is expected to increase the knowledge of the elderly about the benefits of neighborhood health center, thus increasing the activity of which is expected to improve the health status of the elderly. However, the utilization of current Posyandu is still not maximal.Â The purpose of this study is to determine the effect of health promotion to the activeness of elderly to Posyandu. Design used in this study was pre-experimental research with one group- pre and post test approach. Population of the study is and the samples are members of the neighborhood health center anvil Paron II amounted to 12 people.The results showed that an increase in the activity indicated an increase in average attendance from before and after given health promotion that is from 1,33 to 3,75. And increase the probability value active members before and after given health promotion from 0 to 0,208.Data analysis was done by comparing the activity of the elderly before and after treatment, was analyzed manually using descriptive analysis to determine the average value or mean liveliness. From the discussion above shows that there is increased activity of the elderly after given health promotion, this means that health promotion proved to increase the liveliness of the elderly.Â